Performance analysis of wind generators and PV systems in industrial small-scale applications. (August 2019) - Pinheiro, E.; Bandeiras, F.; Gomes, M.; Coelho, P.; Fernandes, J.
Abstract: In this paper, some aspects of the performance of photovoltaic systems and wind generators are discussed. The performance of technologies for different types of wind generators is briefly explained, including the advantages and disadvantages of each type, and for different wind speeds. Technologies and techniques that improve the performance of different photovoltaic systems are also presented in a general way. In addition, a case study is presented to evaluate the use of wind generators and photovoltaic systems for small-scale industrial applications in the Tomar region (Portugal). The approach presented puts the focus on the small-scale applications for small/medium scale industries. These industries have a small/medium power consumption and most of them occupy limited spaces and the environmental conditions are those which exist in the place. The simulations show that there is a significant financial risk associated with the small-scale wind and photovoltaic systems. The purpose of this comparison is to ensure their technical and economic evaluation, leading to a better choice towards achieving zero net energy in buildings. The results obtained for the two technologies allow some important conclusions regarding their applications: photovoltaic systems have better performance than wind generators, photovoltaic systems have high-energy density, which leads to less need for space. Highlights: Performance analysis of small size wind generators and PV systems. Brief review of performance enhancement techniques for PV and WT systems. Evaluation of the WT and PV systems for small-scale industrial applications. Technical and economic comparison of WT and PV small sizes.